PERAN KEPALA SEKOLAH DALAM MELAKSANAKAN MANAJEMEN BERBASIS SEKOLAH DI SMP PEMDA RANTAUPRAPAT - Budi Winata Hasibuan (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The purpose of this research is to know the role of principal of private junior high school in Rantauprapat Local Government in implementing School Based Management either school infrastructure, student, energy, finance, curriculum and school partnership with local community. Methods in this study by used descriptive qualitative research using percentage technique. The instrument of this study used interviews, questionnaire and documentation. The results of this study showed that the percentage results are evident from the results of questionnaires obtained very good as much as 2 respondents where the value is 91-100%. Meanwhile the good rating is 1 respondent where the value is 81-90%. Good enough as many as 14 respondents where the value is from 71-80%. And the selection of Option less good as much as 1 respondent where the value is 61-70%. the conclusion that the percentage from the school principal's role in implementing school-based management at Private Junior High School is good enough overall.